Efeito do revestimento com siloxano-metacrilato após deposição térmica nas propriedades adesivas e mecânicas de pinos de fibra - Reis, Giselle Rodrigues dos (2015)
This study evaluated the effect of thermally deposited siloxane-methacrylate coating on bond strength glass-fiber post to core materials. Furthermore, evaluated mechanical properties of flexural strength, flexural modulus and stiffness. For bond strength, two types of GFP (Exacto, Angelus and White Post DC, FGM) were divided into eight groups (n = 13): S (control): pre-hydrolyzable silane (Prosil, FGM) was applied on the post surface; SA: silane was applied followed by one layer of adhesive (Scothbond, 3M Espe); HS: etching with 35% H2O2 (Whiteness HP Max, FGM) for one minute followed by silane; HSA: etching with H2O2 followed by silane and adhesive; Si: deposited siloxane-methacrylate coating (Si-O) by means of immersion of post in experimental solutions of5% MPTS fowled by heating at 120°C for one hour; SiS: silane application after Si-O; SiA: application adhesive after Si-O; SiSA: silane and adhesive application after Si-O. The composite resin restorations (AllCem Core, FGM) were simulated using translucent silicone molds. After 24 hours water storage at 37 °C, the post/resin assembly was serially sectioned in beams that were subjected to a microtensile bond strength test. For analysis of mechanical properties, eighteen White Post DC and eighteen Exact were used (n = 6). Post without surface treatment, etched with H2O2 and coated with siloxane methacrylate after thermally deposition had their mechanical properties evaluated skin test flexural strength of three points. The data presented normal and homogeneous distribution and subjected to two-way ANOVA and Tukey test. The results showed that the surface treatment only affected the bond strength in Exacto post (P<0.001), while for the White Post DC all groups were statistically equal to the control (22.5 ± 5.1). The highest bond strength values were obtained in SiS (40.4 ± 6.9) and SiSA (38.8 ± 5.3) groups. The etching with H2O2 (HS: 22.9 ± 2.5 and HSA: 25.5 ± 4.5) promoted increased bond strength when compared to control (15.8 ± 4.1), however, had lower values than the thermally deposition siloxane. The mechanical proprieties were not affected by surface treatment, only by the type of post, wherein Exacto post showed highest means of flexural strength, flexural modulus and lower stiffness. Thus, it is concluded that the thermally deposited siloxane-methacrylate coating is a viable option for increasing the bond strength to the core pins without alterations completion of its mechanical properties.